Effect of girdling and foliar spraying of phosphorus on vegetative growth and yield’s quality of two grapevine (Vitis vinifera L.) cultivars Zark and Kamali - Hasan S. Nabi; Naji I. Hussien; Hussien M. Sulaiman; Shawkat M. Muhammed (Kufa Journal for Agricultural Sciences)
This study was conducted during the growing season of 2019-2020 in the vineyard of College of Agricultural Engineering Sciences, University of Duhok, Kurdistan, Iraq to investigate the effect of girdling (girdling and Non-girdling) and spraying of Phosphorus (0, 5, 10 g.L-1) on two grapevine cultivars Zark and Kamali. The results indicated that the girdling led to improve all studied parameters compared with non-girdling one. Girdling of Zark cultivar had a significant effect on number of clusters, shoot length, number of leaves per shoot, number of berries per cluster, total sugar and TSS in berries. Also, the girdling of Kamali cultivar enhanced number of clusters, shoot length, number of shoots per vine, number of leaves per shoot and size of berries. Spraying of phosphorus, especially at 10g.L-1 caused a significant increase in most studied parameters compared to the control. The combination of girdling + 10 g.L-1 of phosphorus with either cultivar was superior treatment for most parameters compared with control of both cultivars.